Influence of retrobulbar tissue acetaldehyde on changes in morphofunctional state of retina, choroid and optic nerve in experimental chronic alcohol intoxication (Ukrainian Journal of Ophthalmology, 2026)
Introduction: Acetaldehyde (AA) is a main mediator of neurotoxicity among methabolites of ethanol (E).Purpose. To study the correlation between concentration of E and AA in retrobulbar tissue (RBT), vitreous humor, blood and morphometric and cytophotometric data of optic nerve, choroid and retina ganglion cells layer in experimental chronic alcohol intoxication.Material and methods. Experimental investigation was performed in 24 male Chinchilla rabbits including 6 rabbits of the control group.Results. Negative correlation (p
Keywords: optic nerve; choroid; retina; retrobulbar tissue; acetaldehyde; chronic alcohol intoxication